INTERLEUKIN-6 AND ACUTE PHASE PROTEINS AS BIOMARKERS OF SEPTIC OSTEOARTHRITIS - Magomedov, Sadrudin; Polyachenko, Yuriy; Hrytsai, Mykola; Litovka, Iryna; Sabodash, Vasyl; Dekhterenko, Natali; Kuzub, Taisiia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Septic arthritis (SA) is a severe and rapidly progressive joint infection and a potentially life-threatening condition that can affect all age groups. Due to the lack of effective methods for early detection and assessment of treatment outcomes, measurement f biochemical markers (biomarkers) is a promising method for monitoring the disease. The aim of the study was to determine the diagnostic significance of inflammatory biomarkers (IL-6, CRP, haptoglobin, ceruloplasmin) in patients with septic joint inflammation of various localizations. Methods. The study analyzed blood serum from 54 male and female subjects. Of these, 18 were conditionally healthy and entered group I (control), and 36 patients were diagnosed with septic osteoarthritis of joints of various localization in the skeleton. Of these, 18 had SA of the knee joint; 13 patients had SA of the hip joint and 5 had SA of the ankle joint. Results. Patients with septic arthritis of the knee and hip joints had significantly increased levels of IL-6 and acute phase proteins in the blood serum. We believe that it is the enhanced synthesis of the pro-inflammatory cytokine IL-6 and acute phase proteins that plays a significant role in the pathophysiology of the inflammatory response, which initiates a chain of reactions that lead to cartilage degradation and further complication of inflammatory processes in the joint. Therefore, these biomarkers can be tools for diagnosing the progression of this disease in both preclinical and clinical studies. The results obtained emphasize the importance of identifying inflammatory biomarkers for diagnosing the progression of septic arthritis in both preclinical and clinical studies to establish the stage of the disease and predict clinical outcome.